The influence of tidal activities on hydrologic variables of Paka river, Terengganu, Malaysia [Pengaruh aktiviti pasang surut bagi variabel hidrologi di sungai Paka, Terengganu, Malaysia] - Mohd Ekhwan, Toriman; Muhammad Barzani, Gasim; Haniff, Muhammad (Malaysian Society of Analytical Sciences, 2015)
A hydrological study was conducted to determine their characteristics at Paka River, Terengganu. Seven sampling stations were identified in this study. Sampling was started from the estuary of Paka River, and ended about 14 km away from the estuary as each station was 2 km apart from each other. Sampling was carried out at two different water tides (low and high water tides) and two durational variations which represented by the wet and dry periods. Hydrological variables such as river velocity, river width and river depth were measured by using specific equipment. River width was measured by using a rangefinder (model Bushnell 20-0001), river depth was measured by using a depth meter (model Speedtech SM-5) and river velocity was measured by using a flow meter/current flow meter (model FP101). Station 1 that located at the downstream identified by highest readings for hydrological variables both water tides during the first and second samplings compared to stations 7 which located at the upstream. Higher readings of hydrological variables were also shown during dry season since low freshwater flow due to less rainfall intensity in the upstream area.